Dos rios ao mar: estudos de genética e conservação de raias (batoidea, elasmobranchii) neotropicais - Pinto, Yan Torres Timbo (2023)
On our planet, the impact of various anthropogenic actions on the environment has led to an increase in the decline and extinction of various species. Among living species, there are some groups that are more vulnerable to anthropogenic impacts than others. Chondrichthyes, the cartilaginous fishes, are an example of these vulnerable groups. Among chondrichthyans, the Batoidea (rays) group is particularly diverse and has more species that are threatened in some way, but it has received less attention in research. Therefore, the development of such studies is important for the formulation of effective management and conservation strategies. In this context, the goal of this study is to develop research that can support the development of conservation measures for Neotropical batoids. The first chapter provided the first confirmation of multiple paternity in the subfamily Potamotrygoninae. This confirmation expands the understanding of the reproductive aspects of the group and opens up possibilities for understanding the polychromatism observed in many species. In the second chapter, the population structure of the Brazilian Guitarfish (Pseudobatos horkelii) is analyzed. At least two groups were identified between which significant genetic differences exist at the population level. These data should be considered in management plans aimed at maintaining the genetic diversity of this species. The third chapter reviews the known genetic data of the Neotropical freshwater ray group. This work identified and analyzed the studies conducted to date, the knowledge gaps that exist, and the possible alternatives to fill them. In the fourth chapter, an analysis of the main threats to Potamotrygoninae species was carried out. Based on the results, it was possible to design management perspectives and measures for the group, taking into account regional differences. In the fifth chapter, polychromatic dorsal diversity in Potamotrygon leopoldi was evaluated. Ontogenetic variation in coloration was described in this species, and coloration patterns associated with location were identified. These data are important tools for export monitoring and can be used to support enforcement actions. Thus, the studies presented provide an important contribution of information for the management and conservation of Neotropical batoid species.